إدارة السمعة والمنهج النبوي: دراسة موضوعية تحليلية - كمالي، أحمد إسماعيل عبد الله إسماعيل (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study aims at demonstrating the science of modern reputation management and to scrutinize it based on the Prophetic approach. It highlights the most important factors affecting reputation at all levels. It clarifies the required principles and behavioural values for forming good reputation and its effect on individuals, societies, institutions and countries. The study also pinpoints the importance of means of communication in the process of reputation management. It covers the most important strategies to deal with the challenges that might affect reputation management. In his conclusion, the researcher suggests a practical approach for managing institutional reputation. To meet the objectives of the study, the researcher adopts two main approaches: first, inductive approach selecting one hundered and twenty nine prophetic traditions which are relevant to subject of the study from Sahih Al-Bukhari and their importance in forming reputation based on the Prophets' methods. Second, analytical approach to drive out the evidence from such Hadiths that reflect the Prophet's approach in managing reputation. The researcher has concluded his study with many results, the most important of them is the fact that the factors that affect institutional reputation which have been introduced by modern reputation management are the same factors found in the Prophetic approach for reputation management. Moreover, the Prophet applied and acted according to them. The Prophetic approach for reputation management has been distinguished with being comprehensive and of gradual application. The Prophet starts by forming his reputation and then the reputation of his family and then the society. This gradualism has resulted in the acceptance of his Message. The researcher has introduced some important recommendations, the most important of them is his invitations to governmental and private institutions to avail benefit from the practical approach to develop effective institutional management. He also urges other researchers to introduce applied and experimental studies in the field of reputation management at the level of governmental and private institutions.